2011
DOI: 10.1074/jbc.m111.279687
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the Peroxisome and β-Oxidation Cycle to Biotin Synthesis in Fungi

Abstract: Background: Pimeloyl-CoA is an intermediate of the biotin pathway, but it is unknown how it is synthesized in fungi. Results: Aspergillus nidulans mutants in ␤-oxidation are biotin-deficient, and the enzyme utilizing pimeloyl-CoA is targeted to the peroxisome. Conclusion: Pimeloyl-CoA is synthesized in the peroxisome via the ␤-oxidation cycle in filamentous fungi. Significance: This is the first implication of peroxisomal ␤-oxidation in biotin synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…Finally, we also considered biotin to be a rescue factor for the mfe2⌬ mutant because the biotin biosynthetic pathway in fungi might be located in the peroxisome and its precursor (pimelic acid) might depend on ␤-oxidation activity (46). In a spot test, we found that biotin also showed a weak rescue activity for the mfe2⌬ mutant (Fig.…”
mentioning
confidence: 86%
“…Finally, we also considered biotin to be a rescue factor for the mfe2⌬ mutant because the biotin biosynthetic pathway in fungi might be located in the peroxisome and its precursor (pimelic acid) might depend on ␤-oxidation activity (46). In a spot test, we found that biotin also showed a weak rescue activity for the mfe2⌬ mutant (Fig.…”
mentioning
confidence: 86%
“…In addition, the fast-growing biotin-prototrophic strains described in this study provide interesting experimental platforms for unraveling the elusive biochemistry of pimelate biosynthesis in S. cerevisiae and other yeasts (10,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Starting from pimelic acid, biotin biosynthesis in prototrophic yeast strains follows the prokaryotic pathway ( Fig. 1), but the yeast pathway for synthesis of this key precursor has not yet been fully elucidated (10,12,13). Biotin biosynthesis genes in yeast are assumed to have been at least partially acquired from anaerobic bacteria by horizontal gene transfer, followed by gene duplication and neofunctionalization events (14,15).…”
mentioning
confidence: 99%
“…The first enzyme in biotin synthesis (BioF) is peroxisomal in plants and fungi [3,4], while the subsequent steps are mitochondrial. Moreover, peroxisomal β-oxidation is required for synthesis of the BioF substrate, pimeloyl-CoA [3,4].…”
Section: Functional Diversity Of Plant Peroxisomesmentioning
confidence: 99%